Vaping: A Safe Alternative to Counteract Smoking? Case Report - María Cristina Martínez-Ávila; Eugenio Matijasevic Ardila; Alieth Lucía Acosta Cardozo; Cristian Camilo Alvarado Castro; Carlos Eduardo Matiz-Bueno (Clinical Medicine Insights: Case Reports)
The respiratory impact of e-cigarette usage, also known as vaping, emerged as a significant healthcare issue in 2019. This concern arose due to the sharp rise in cases of e-cigarette or vaping-associated lung injury (EVALI) among adolescents and young adults. Now, systemic manifestations have been described. We present the case of a 39-year-old male patient who had been vaping for 5 years and developed EVALI associated with multiple severe complications, including acute myocardial infarction, metabolic acidosis, acute kidney injury and sepsis-like syndrome, requiring hospitalization in the critical care unit. Every day, reports of patients with systemic complications due to the use of e-cigarettes are becoming more frequent. Therefore, it is crucial for clinicians to be aware of this condition and to consider whether vaping truly constitutes a safe alternative to combat smoking.